2001
DOI: 10.1023/a:1012231020944
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Pine weevils (Hylobius abietis) fed less on bark of lodgepole pine (Pinus contorta) than on bark of Scots pine (P. sylvestris). Two pine weevil antifeedants, ethyl trans-cinnamate and ethyl 2,3-dibromo-3-phenyl-propanoate, were isolated from bark of lodgepole pine. These two compounds significantly reduced pine weevil feeding in a laboratory bioassay. In field assays, the second compound significantly decreased pine weevil damage on planted seedlings. Ethyl 2,3-dibromo-3-phenylpropanoate has not previously bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…In the present study the mean debarked area did not differ between Norway spruce and Scots pine seedlings, but significantly more feeding damage was found on Sitka spruce, showing that there are also differences within the genus Picea. The pine weevil consumed less bark on lodgepole pine than on Scots pine seedlings, possibly because antifeedant compounds that have been identified in lodgepole pine but not in Scots pine influence weevil feeding preferences (Bratt et al 2001). Several field and laboratory experiments have also shown that larch is a less attractive food source than Norway spruce and Scots pine (Löf et al 2004;Olenci and Olenci, 2003), and billets of Sitka spruce reportedly attract more pine weevils than larch billets (Wilson and Day 1995).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study the mean debarked area did not differ between Norway spruce and Scots pine seedlings, but significantly more feeding damage was found on Sitka spruce, showing that there are also differences within the genus Picea. The pine weevil consumed less bark on lodgepole pine than on Scots pine seedlings, possibly because antifeedant compounds that have been identified in lodgepole pine but not in Scots pine influence weevil feeding preferences (Bratt et al 2001). Several field and laboratory experiments have also shown that larch is a less attractive food source than Norway spruce and Scots pine (Löf et al 2004;Olenci and Olenci, 2003), and billets of Sitka spruce reportedly attract more pine weevils than larch billets (Wilson and Day 1995).…”
Section: Discussionmentioning
confidence: 99%
“…However, in that experiment, the native species reportedly had higher tolerance to the damage. The differences between tree species in the extent of feeding damage are probably related to variation in chemical composition, influencing the quantity of phloem tissue consumed by the pine weevil (Bratt et al 2001;Carillo-Gavilán 2012;Moreira et al 2013). Induction of resin in the stem and phloem after wounding as well as nitrogen concentration has been found to vary between tree species, and may contribute to variation in the amount of pine weevil feeding (Wainhouse et al 2004;Zas et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of environmental hazards and health risks for forest workers the usage of insecticides is seriously questioned today. Possibly, antifeedant substances applied to transplants could offer an alternative to insecticides [2].…”
Section: Introductionmentioning
confidence: 99%
“…To confirm the pine weevil antifeedant activity of the three major compounds identified in the emissions of isolated bacterial isolates, feeding tests were made by means of a two-choice laboratory bioassay, used in several previous studies [10, 1215, 27]. 2-Phenylethanol and 2-methoxyphenol were tested in the concentrations 5, 25, and 50 mM, while for phenol only 50 mM was used.…”
Section: Methodsmentioning
confidence: 99%